Structural and photoluminescence properties of CdO doped TiO2 thin films prepared by pulsed laser deposition - Mohammed, Ghusson H. (Iraqi Journal of Physics, 2019)
TiO2 thin films have been deposited at different concentration ofCdO of (x= 0.0, 0.05, 0.1, 0.15 and 0.2) Wt. % onto glass substratesby pulsed laser deposition technique (PLD) using Nd-YAG laserwith λ=1064nm, energy=800mJ and number of shots=500. Thethickness of the film was 200nm. The films were annealed todifferent annealing (423 and 523) k. The effect of annealingtemperatures and concentration of CdO on the structural andphotoluminescence (PL) properties were investigated. X-raydiffraction (XRD) results reveals that the deposited TiO2(1-x)CdOxthin films were polycrystalline with tetragonal structure and manypeaks were appeared at (110), (101), (111) and (211) planes withpreferred orientation along 2Ɵ around 27.30. The results ofphotoluminescence (PL) emission show that there are two peakspositioned are around 320 nm and 400 nm for predominated peakand 620 nm and 680 nm for the small peaks.